1998
DOI: 10.1089/hum.1998.9.3-353
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Stromal Cells as Targets for Gene Therapy of Hemophilia A

Abstract: Attempts to develop an ex vivo gene therapy strategy for hemophilia A, using either primary T cells or bone marrow (BM) stem/progenitor cells have been unsuccessful, due to the inability of these cell types to express coagulation factor VIII (FVIII). As an alternative, we evaluated the potential of BM-derived stromal cells which can be readily obtained and expanded in vitro. Human and murine BM stromal cells were transduced with an intron-based Moloney murine leukemia virus (MoMLV) retroviral vector expressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 42 publications
2
84
1
Order By: Relevance
“…In a related study, transgene expression from murine stem cell virus-based vectors in vivo lasted for up to 12 weeks in human MSCs, adhered to ceramic cubes and implanted into severe combined immunodeficient (SCID) mice [15]. However, transduction of MSCs with MoMLV and murine stem cell virus-based vectors were shown to be inefficient, as they required drug selection to enrich transduced cells [13,15], multiple rounds of transduction for several days [14,16,17], or highly concentrated vector stocks [18]. In addition, efficient transduction of human MSCs by amphotropic MoMLV and murine stem cell virus pseudotypes was found to be limited by the expression levels of the amphotropic viral receptor.…”
Section: Transgene Delivery Into Mesenchymal Stem Cells Using Viral Vmentioning
confidence: 99%
See 2 more Smart Citations
“…In a related study, transgene expression from murine stem cell virus-based vectors in vivo lasted for up to 12 weeks in human MSCs, adhered to ceramic cubes and implanted into severe combined immunodeficient (SCID) mice [15]. However, transduction of MSCs with MoMLV and murine stem cell virus-based vectors were shown to be inefficient, as they required drug selection to enrich transduced cells [13,15], multiple rounds of transduction for several days [14,16,17], or highly concentrated vector stocks [18]. In addition, efficient transduction of human MSCs by amphotropic MoMLV and murine stem cell virus pseudotypes was found to be limited by the expression levels of the amphotropic viral receptor.…”
Section: Transgene Delivery Into Mesenchymal Stem Cells Using Viral Vmentioning
confidence: 99%
“…The amphotropic receptor is a phosphate transporter whose expression is increased in the absence of phosphate. Chuah et al [16] used a phosphate starvation procedure to increase transduction of MSCs by amphotropic MoMLV-based vectors.…”
Section: Transgene Delivery Into Mesenchymal Stem Cells Using Viral Vmentioning
confidence: 99%
See 1 more Smart Citation
“…This list includes the replacement of genes to correct acquired or inherited disorders of bone, muscle, or cartilage by transfer of genes encoding bone morphogenic proteins -2, -4, -9 [21,[32][33][34][35][36][37][38][39][40], the transfer of genes encoding the blood coagulation factors VIII and IX for the treatment of hemophilia [41][42][43][44][45][46][47], human growth hormone [46,48], insulin-like growth factor 1 [49], and interleukin-3 [50]. This list also includes: erythropoietin [51], α-l-iduronidase for treatment of mucopolysaccharidosis type I [52], proα2 collagen (I) for treatment of osteogenesis imperfecta [53], sox9 [54] to enhance chondrogenesis, and interferon to treat tumors [55].…”
Section: ® Original Articlementioning
confidence: 99%
“…These data are consistent with those of other investigators who have shown long-term and high-level expression of transgenes in mice or rats transplanted with MFG-transduced hematopoietic cells. [22][23][24] Concordant with the high level enzymatic expression, an almost complete correction of the reticuloendothelial system pathology, which was observed only when high-level engraftment (ie Ͼ90%) was achieved by BMT, 18 was seen in gene therapy-treated animals engrafted 30% or less.…”
Section: Discussionmentioning
confidence: 81%